Enhancing Microstrip Antenna Performance with Metamaterial Structures: “A Parametric Study on S-Parameters and Radiation Characteristics” - Bambang Bagus H; Achmad Setiyo p; Ade Irfansyah; Yuyun Suprapto; Nyaris Pambudiyatno; Teguh Imam Suharto; Hadi Setiyo Prayitno (Universitas Trunodjoyo Madura, 2025)
Microstrip antennas play a crucial role in modern wireless communication systems owing to their compact geometry, low manufacturing cost, and ease of integration with planar circuitry. Despite these advantages, conventional microstrip antennas encounter inherent limitations such as narrow bandwidth, low gain, and reduced radiation efficiency. To overcome these challenges, this study introduces an improved antenna configuration incorporating metamaterial structures—particularly the Split-Ring Resonator (SRR) and the Electromagnetic Band Gap (EBG)—designed to enhance electromagnetic performance through surface-wave suppression and resonance manipulation. A rigorous simulation procedure using CST Microwave Studio is employed to analyze the effects of metamaterial placement and geometric optimization. The investigation focuses on key performance parameters, including S-parameters (S11, S21), bandwidth, radiation patterns, gain, and radiation efficiency. Through parametric evaluation, the integration of metamaterials is expected to significantly improve impedance matching, broaden operational bandwidth, and enhance radiation stability compared to conventional designs. The results of this work are anticipated to provide meaningful insights into how metamaterial structures can reshape current distribution and modify antenna behavior across targeted frequency bands. These findings contribute valuable knowledge for developing high-efficiency antennas suitable for next-generation wireless technologies, particularly millimeter-wave applications, IoT devices, and high-frequency communication systems.